Attention alters predictive processing. (2016) - Clark, Andy
Abstract: Firestone & Scholl (F&S) bracket many attentional effects as "peripheral, " altering the inputs to a cognitive process without altering the processing itself. By way of contrast, I highlight an emerging class of neurocomputational models that imply profound, pervasive, nonperipheral influences of attention on perception. This transforms the landscape for empirical debates concerning possible top-down effects on perception.